The learning curve for laparoscopic-assisted single-port mediastinoscopic esophagectomy: an analysis of proficiency - Wenhao Li; Xiangfeng Gan; Liangzhan Lv; Yingmeng Wu; Weizhao Huang; Yi Liang; Qingdong Cao (BMC Surgery)
Abstract Background Laparoscopic-assisted single-port mediastinoscopic esophagectomy is a safe and effective emerging minimally invasive esophagectomy, but little has been reported about the learning curve for this technology. The goal of the study was to determine the number of procedures to achieve different levels of proficiency on the learning curve. Methods This study retrospectively analyzed data from consecutive surgeries performed by the same surgeon at the same center from 2016 to 2021. Learning curves were quantitatively assessed by unadjusted cumulative sums, different segments were derived using jointpoint linear regression analysis, and variables were compared between subgroups using trend analysis. Results The learning curve could be divided into 3 different proficiency stages: the 1st-91st, 91st-125th, and 125th-182nd procedures comprised the preliminary, transition, and proficient stages, respectively. Compared with the preliminary stage, the procedure time [275 (250–300) vs 178.5 (161.5–205.0) min, P < .001], bleeding volume [100 (100–200) vs 50 (50–80) mL, P < .001], postoperative hospital stays [15 (13–31) vs 13 (11–17) d, P = .006], and the incidence of anastomotic fistula(20.9% vs 5.2%, P = .017) were significantly lower in the proficiency stage, whereas the number of harvested total lymph nodes [17 (12–23) vs 22 (16–29), P = .002], total mediastinal lymph nodes [7 (5–11) vs 13 (9–18), P < .001] and the rate of recurrent laryngeal nerve lymph node harvest (71.4% vs 96.6%, P < .001) was significantly higher. Conclusions There may be 3 stages of varying proficiency in the learning curve of laparoscopic-assisted single-port mediastinoscopic esophagectomy. Approximately 91 consecutive procedures were required to overcome the preliminary stage, whereas proficiency in this technique required approximately 125 consecutive procedures.